New Genomic Approaches to Enhance Biomass Degradation by the Industrial Fungus Trichoderma reesei - Renato Graciano de Paula; Amanda Cristina Campos Antoniêto; Liliane Fraga Costa Ribeiro; Cláudia Batista Carraro; Karoline Maria Vieira Nogueira; Douglas Christian Borges Lopes; Alinne Costa Silva; Mariana Taíse Zerbini; Wellington Ramos Pedersoli; Mariana do Nascimento Costa; Roberto Nascimento Silva (International Journal of Genomics)
The filamentous fungi Trichoderma reesei is one of the most well-studied cellulolytic microorganisms. It is the most important fungus for the industrial production of enzymes to biomass deconstruction being widely used in the biotechnology industry, mainly in the production of biofuels. Here, we performed an analytic review of the holocellulolytic system presented by T. reesei as well as the transcriptional and signaling mechanisms involved with holocellulase expression in this fungus. We also discuss new perspectives about control of secretion and cellulase expression based on RNA-seq and functional characterization data of T. reesei growth in different carbon sources, which comprise glucose, cellulose, sophorose, and sugarcane bagasse.